Long‐term follow‐up of children exposed intrauterine to maternal thiopurine therapy during pregnancy in females with inflammatory bowel disease. Issue 1 (16th May 2013) - de Meij, T. G. J.; Jharap, B.; Kneepkens, C. M. F.; van Bodegraven, A. A.; de Boer, N. K. H.; ,
Summary: Background: Inflammatory bowel disease (IBD) affects a substantial number of female patients in their reproductive years. Therefore, many physicians face the dilemma whether thiopurines, prescribed to maintain remission, can be taken safely during pregnancy. Data on long‐term development outcome of children exposed to maternal thiopurine therapy are very limited. Aim: To assess the long‐term effects of in utero exposure to thiopurines during pregnancy on infant health status. Methods: A prospective multicentre follow‐up study was performed in children exposed intrauterine to maternal thiopurine therapy. Physical, cognitive and social aspects of infant health status were assessed with the 43‐item TNO‐AZL Preschool Children Quality of Life Questionnaire (TAPQOL). Furthermore, information on visits to general practitioner and medical specialists, and physician's advice regarding lactation was evaluated. Data were compared with normative data from a control group consisting of 340 children. Results: Thirty children were included in this study [median 3.8 years (IQR 2.9–4.7)]. No differences on global medical and psychosocial health status were found between children exposed to intrauterine thiopurines and the reference group. Exposure to intrauterine thiopurines was not associated with increased susceptibility to infection or immunodeficiency in childhood. Twenty‐one of 30 children were exclusively formula‐fed based on a negative advice of medical specialists directed at thiopurine use during lactation. Conclusions: Thiopurine use during pregnancy did not affect long‐term development or immune function of children up to 6 years of age. Our results underscore the present notion that mothers, even those using thiopurines, should be encouraged to breastfeed their infants.